Musical doce solidão - Vaz, Ana Laura de Fendi [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research presents the steps taken on the working process the Doce Solidão project. It consists on the production of a short musical film, with approximately 30 minutes of duration. The project has as objective to value the national culture by using music written by Brazilian artists to tell a story, and also contribute to the musical audiovisual scenery. The film tells the story of four characters from the point of view of Edu, a shy and passionate young man. The songs are included on the narrative in order to express their thoughts, feelings and some situations experienced by them. Besides the film production report, this paper also includes a study of music history in cinema and its functions, video clips language and aesthetics, techniques used in musical film productions and a historical background of the musical cinema in Brazil and worldwide

Esta pesquisa apresenta as etapas da elaboração do projeto Doce Solidão. O projeto consiste na produção de um curta-metragem de gênero musical, com duração aproximada de 30 minutos. O projeto tem como objetivo valorizar a cultura nacional utilizando músicas de artistas brasileiros para contar uma história, além de contribuir para o cenário audiovisual de gênero musical. O filme conta a história de quatro personagens a partir da vida de Edu, um garoto tímido e apaixonado. As músicas são incluídas na narrativa para expressar os pensamentos, sentimentos e determinadas situações pelas quais passam os personagens. Além do relatório de produção do filme, o trabalho conta também com um estudo da história da música no cinema e quais suas funções, da linguagem e estética de videoclipes, técnicas utilizadas em produções musicais e um histórico do cinema musical no Brasil e no mundo
Keywords: Curta-metragem; Gravações de video - Produção e direção; Trilhas sonoras para cinema; Cinema sonoro; Filmes musicais; Film soundtracks